Do we need to change empiric antibiotic use following natural disasters? A reflection on the Townsville flood. Issue 1 (1st November 2021) - Jenkin, Ashley; Mantha, Pranay; Palamuthusingam, Pranavan
Abstract: Introduction: Skin and soft tissue infections have the potential to affect every patient admitted to a surgical service. Changes to the microbiota colonizing wounds during natural disasters, such as the Townsville floods of 2019, could impact empiric antibiotic choice and need for return to theatre. Methods: This retrospective observational cohort study reviews culture data and demographics for patients undergoing surgical debridement of infected wounds over a six‐month period starting in November 2018 to May 2019 at the Townsville Hospital. Results: Of the 408 patients requiring operative intervention, only 61 patients met the inclusion criteria. The groups were comparative in terms of age and gender, but a greater proportion of patients (40.5% versus 29.1%, P = 0.368) in the post‐flood group were diabetic. Common skin commensals, such as Staphylococcus aureus, were the most common pathogen in both groups, however the post‐flood group had a higher proportion of atypical organisms (14 versus 8 patients), and an increased need for repeated debridement for infection control (24 versus 14 patients). Conclusion: Wound swabs and tissue culture are imperative during surgical debridement and may guide the use of more broad‐spectrum coverage following a significant flooding event. Abstract : This retrospective observational cohort study examines the empiric use of antibiotics following the flooding disaster in Townsville in 2019 and the corresponding shift in pathogens involved in surgical wounds requiring debridement. We recommend swab and tissue sampling for all patients undergoing surgical debridement and consideration of broad‐spectrum antibiotics following a flooding event.